2015
DOI: 10.1007/s00431-015-2512-x
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of the effectiveness of zinc in diarrhoea of children living in Switzerland

Abstract: zinc treatment decreases the frequency and severity of diarrhoea in children aged 2 months to 5 years living in Switzerland. However, the intention-to-treat analysis reveals compliance issues that question the proper duration of treatment and the choice of optimal pharmaceutical formulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 15 publications
2
29
0
Order By: Relevance
“…A meta-analysis (including 18 clinical trials with 6165 participants) showed that zinc supplementation resulted in a shorter diarrhea duration in acute diarrhea, and less diarrhea at Day 3 and Day 5, similar to our results (17). In contrast to other studies, a recently made double-blind randomized study about zinc supplementation for acute diarrhea in Switzerland showed that zinc treatment decreases the frequency and severity of diarrhea in children aged 2 months to 5 years old, but not the duration of diarrhea (20). In developing countries, zinc supplementation might be useful in the treatment of acute diarrhea for children older than 6 months.…”
Section: Discussionsupporting
confidence: 88%
“…A meta-analysis (including 18 clinical trials with 6165 participants) showed that zinc supplementation resulted in a shorter diarrhea duration in acute diarrhea, and less diarrhea at Day 3 and Day 5, similar to our results (17). In contrast to other studies, a recently made double-blind randomized study about zinc supplementation for acute diarrhea in Switzerland showed that zinc treatment decreases the frequency and severity of diarrhea in children aged 2 months to 5 years old, but not the duration of diarrhea (20). In developing countries, zinc supplementation might be useful in the treatment of acute diarrhea for children older than 6 months.…”
Section: Discussionsupporting
confidence: 88%
“…Seventeen trials only enrolled children over six months of age (Sachdev 1988; Sachdev 1990; Sazawal 1995; Bhutta 1999; Faruque 1999; Penny 1999; Khatun 2001; Bahl 2002; Strand 2002; Boran 2006; Roy 2008a; Fajolu 2008; Patel 2009; Dutta 2011; Karamyyar 2013; Passariello 2015; Tran 2015). Fourteen trials included children of different ages greater than one month (Roy 1997; Roy 1998; Dutta 2000; Al-Sonboli 2003; Polat 2003; Bhatnagar 2004a; Larson 2005; Shimelis 2008; Patro 2010; Dalgic 2011; Jin 2013; Crisinel 2015; Patel 2015; Jiang 2016). …”
Section: Resultsmentioning
confidence: 99%
“…Only three trials were conducted in Europe (Patro 2010; Crisinel 2015; Passariello 2015), two in South America (Al-Sonboli 2003; Penny 1999), two in Africa (Fajolu 2008; Shimelis 2008), one multicentre trial in Asia and Africa (Fischer Walker 2006), and one trial in Australia (Tran 2015). Thus, participants were from Bangladesh (Roy 1997; Roy 1998; Faruque 1999; Khatun 2001; Brooks 2005a; Larson 2005; Roy 2008a), India (Sachdev 1988; Sachdev 1990; Sazawal 1995; Dutta 2000; Bahl 2002; Bhatnagar 2004a; Fischer Walker 2006 IND; Patel 2009; Patel 2015), Pakistan (Bhutta 1999; Fischer Walker 2006 PAK), Nepal (Strand 2002), China (Jin 2013; Jiang 2016), Turkey (Polat 2003; Boran 2006; Dalgic 2011), Brazil (Al-Sonboli 2003), Peru (Penny 1999), Ethiopia (Fischer Walker 2006 ETH; Shimelis 2008), Nigeria (Fajolu 2008), Poland (Patro 2010), Italy (Passariello 2015), Switzerland (Crisinel 2015), and Australia (Tran 2015). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors made no comment with regard to funding or potential bias. Despite having identical treatment arms, Crisinel et al ’s11 2015 study of 87 children aged between 2 and 60 months in one hospital in Switzerland elicited different results. Per-protocol analysis showed significantly shorter median duration of diarrhoea in the zinc arm.…”
Section: Commentarymentioning
confidence: 99%